Reconstruction of Employment Regulations that are Integral in Realizing Industrial Relations Based on Pancasila Justice - subiyanto, Subiyanto; Endah Wahyuningsih, Sri; Hafidz, Jawade; Mashdurohatun, Anis (International Journal Labs, 2025)
This research aims to analyze and discover the extent of the application of the value of Pancasila justice in labor regulations, both the legal structure, the substance of the legal material and the legal culture. To analyze and find the weaknesses of the application of the value of Pancasila justice in labor regulations to reconstruct Indonesian labor regulations, in realizing harmonious, dynamic and fair industrial relations based on the value of Pancasila justice. The sociological juridical research method is an approach to seeing a legal reality in society, this approach uses secondary data as the initial data which is then followed by primary data or field data, with the nature of analytical descriptive research. The theoretical foundation in this dissertation uses the theory of Pancasila justice, the theory of the legal system, the integrative theory and the theory of legal development, as well as the theory of legal protection and the theory of legal certainty. That the substance of the law is the part that determines the direction of law implementation and forms legal culture. The results of research on the construction of existing labor regulations have not been able to realize just industrial relations, because the legal substance (substance of the law) does not yet contain Pancasila justice values ??in labor regulations on an ideal and operational basis, so that a legal culture of dialogue has not yet been realized.